Migration processes in the Republic of Kazakhstan: regularities, problems, and prospects - Kappassova, Gulsara (Dve domovini, 2024)
The study’s relevance lies in the ongoing phenomenon of mass migration, which significantly impacts society, economy, and politics worldwide. The purpose is to consider the features of the current situation in the migration field in Kazakhstan and assess the possibilities for public policy development. In this study, the problem-thematic method and the method of policy analysis were used. The study emphasizes the role of migration trends in Kazakhstan and the impact on its socioeconomic, demographic, cultural, and political development. Special attention is paid to integrating global trends and socioeconomic prerequisites for the reception of migrants.
Keywords: dejavniki migracij; globalizacija; globalization; migracije; migracijska politika; migracijska tveganja; migracijski potencial; migration; migration factors; migration policy; migration potential; migration risks